2013
DOI: 10.1007/s13139-013-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of PET Template-Based Analysis on F-18 FP-CIT PET in Patients with De Novo Parkinson’s Disease

Abstract: Quantitative parameters using FP-CIT PET template-based method correlated well with those using laborious manual method with excellent concordance. Moreover, PET-based quantitation was less influenced by the reference region than MR-based method. It suggests that PET-based method can provide objective and quantitative parameters quickly and easily as a feasible analysis in place of conventional method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…18 F‐FP‐CIT PET/CT scans were performed using a methodology described previously (Jeong et al, ). Patients were intravenously injected with 18 F‐FP‐CIT (185 MBq), and PET/CT was performed 3 h after injection using a PET/CT scanner (Biograph 6 TruePoint True V, Siemens Medical Solutions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F‐FP‐CIT PET/CT scans were performed using a methodology described previously (Jeong et al, ). Patients were intravenously injected with 18 F‐FP‐CIT (185 MBq), and PET/CT was performed 3 h after injection using a PET/CT scanner (Biograph 6 TruePoint True V, Siemens Medical Solutions).…”
Section: Methodsmentioning
confidence: 99%
“…SBR was defined using the following formula: (Mean count of each region – mean count of reference tissue)/mean count of the reference tissue. PCR was defined as the ratio of the mean count in the bilateral putamina to the mean count in the bilateral caudate nuclei (Jeong et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, ligand-specific template for presynaptic dopaminergic nerve terminal imaging had been used in several clinical studies without proper validation [ 19 , 23 , 24 ]. One study showed the feasibility of ligand-specific [ 18 F]-FP-CIT PET template and good correlation between the striatal binding and clinical severity scores [ 25 ]. Since only the PD patients were analyzed, they might have missed the unbalanced overestimation of striatal binding between the PD patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, objective image quantification using SPAM has been widely studied in PET data such as 18 F-FP-CIT PET for dopamine transporter imaging [18,19]. Although SPAMbased quantification provided the objective parameters, the previous methods were descriptive and did not preserve anatomical information [8,10].…”
Section: Discussionmentioning
confidence: 99%